AN APPRAISAL OF KANT’S DEONTOLOGY AS A REMEDY TO MORALITY CHALLENGES IN NIGERIA - AMADI, Uchendu Cyprian; Nwinya, Stephen Chijioke; OGBU, Chukwunonso Kingsley (EBSU Journal of Social Sciences and Humanities, 2024)
The moral fallout in our today society, particularly Nigeria, gets one irritated when pondered upon. Agreeably that, the experiences of the decades gone by in Nigeria has shown that the country has been faced with morality challenges in every facet of her existence, a situation that is deteriorating continually every passing day. The diverse cultural values of indigenous Nigeria have been neglected in favour of western values. Moral perversity is prevalent in the society, and there is conspicuous lack of sense of commitment among leaders. The quest to assume offices in the country is not for the sense of duty, but a crazy quest to amass and embezzling the public funds. Corruption has assumed a way of life, conspicuous in both private and public engagement. Moral values among the youths are in jeopardy as sense of morality, commitment and duty has been sacrificed on the altar of get-rich-quick-syndrome. More disturbing is the recent wave of "education is a scam". This height of moral decay affecting all facets of Nigeria’s national necessitated this paper. The idea is that exposition of Kant’s deontology with its call on individual to duty might sting Nigerians to moral evaluation of the engagement. This paper is timely in positing a moral sense of collective duty among every Nigerian citizen, as Immanuel Kant postulated in his deontology. No doubt, this will be a key to cub web the morality challenges facing the country. To achieve this, this paper will be using expose Kant’s deontology and critically analyse the sources of moral challenges in Nigeria and then conclude that emphasis on sense of morality and duty in all spheres of national life is the solution to moral challenges in Nigeria.